Transformation of Library Mobile Services: New Innovations in Information Literacy and Collection Access - Azzahro, Atika; Reni, Okta (UIN Raden Intan Lampung, 2025)
This study discusses the transformation of mobile library services as an innovation in supporting information literacy and access to digital collections. The development of information technology in the digital era has changed the way people access and utilize information, requiring libraries to innovate through mobile-based services that allow access anytime and anywhere. Mobile libraries are an innovation that integrates digital collections, interactive features, and electronic lending systems to improve information literacy and equalize access to information. This study uses a literature review approach with data collection through the iPusnas, iJakarta, and several other mobile library applications. The data obtained was then triangulated to ensure validity. The analysis focused on three main aspects of mobile library services, namely information transparency, information retrieval, and digital service accessibility. The results of the study show that mobile libraries have implemented the principle of transparency by providing clear information on services, borrowing policies, and collection availability. In terms of information retrieval, there are search features based on title, author, category, and keywords that make it easy for users to find information. In terms of accessibility, the application is designed with a simple display, easy navigation, and flexible access via mobile devices This transformation of mobile library services supports information literacy, expands access to digital collections, and strengthens reading culture. It is also expected to serve as a reference for further research.